Voltage Instability Analysis For Electrical Power System Using Voltage Stability Index - Amar Hakimi, Bahar (2022)
The rise of voltage instability phenomena from the past few decades until now is worrying. The increases of power demand and limited power sources make the system to operate at its maximum limit of capacity. When the system is working at its limit, this situation can lead to voltage stability problems such as voltage collapse. Hence, it is important to identify the voltage stability weak areas to avoid the voltage collapse. This paper will present the study of voltage instability analysis using pre-developed voltage stability index, Fast Voltage Stability Index (FVSI) as the main index. The Line Stability Index (Lmn) is also will be use to determine voltage instability activity. Voltage instability analysis can be done with many ways. One of it by increase the load at selected bus. The loading will be injected until the bus reach its maximum loadability. At this point, the system will experience a sudden voltage drop as the index reaching to 1 and the system is now considered as voltage collapse. In this paper, the line outage will be carrying out to observe the voltage and Fast Voltage Stability Index values. The line outage most likely will affect the voltage condition of the system. Both of analysis will be test on IEEE-30 bus system and IEEE-69 bus system and this project will fully work on MATLAB software.